THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, MOTIVATION, AND COMPENSATION ON EMPLOYEE PERFORMANCE: LITERATURE REVIEW - Rahma Insani, Fitri Amalia; Hadi, Syamsul; Yulianto, Eko (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Abstract Employee performance is a crucial aspect in a company because the development of a company is inseparable from the performance of its employees. Therefore, it is important to understand the factors that support the performance of an employee. This article aims to comprehend the literature review regarding the influence of transformational leadership, motivation, and compensation on employee performance. The research method employed is a systematic literature review (SLR) using 18 journals and articles obtained from Google Scholar and the National Library with keywords